The Effect of Leadership and Work Stress on Turnover Intantion And Their Impact on Job Satisfaction - Serianis; Adi Rahmat; Jeni Wardi (Yayasan Education Al Aqsho Modern, 2023)
This study aims to analyze the influence of leadership, and work stress on the desire to move which has implications for employee satisfaction the population in this study are employees of PT. Bank BPR Tuah Negeri Mandiri, totaling 48 people. The data analysis technique used is Structural Equation Model (SEM) modeling using the Partial Least Square (PLS) program. The SEM-PLS evaluation model is based on prediction measurements that have nonparametric properties. The results showed that: (1) leadership has a significant effect on turnover intention, with an effect of 0.45, (2) leadership has a significant effect on job satisfaction, with an effect of 0.43, (3) job stress has a significant effect on desire Switching has an effect of 0.39, (4) Job Stress has a significant negative effect on Job Satisfaction with an effect of -0.26, (5) Desire to Move has a significant negative effect on Job Satisfaction, with an effect of -0.28.